Frequency and causes of blindness and visual impairment in schools for the blind in Yaoundé (Cameroon) - Noche, Christelle Domngang; Bella, Assumpta Lucienne (Santé (Montrouge, France), 2010)
To determine the causes of blindness and visual impairment in students attending schools for the blind in Yaounde (Cameroon) and to estimate their frequencies. This study examined all 56 students at three schools for the blind in Yaoundé from September 15 through October 15, 2006. We collected data about their age, sex, medical and surgical history. Visual acuity was measured to determine their vision status according to the World Health Organization categories for blindness and visual impairment. All subjects underwent an ocular examination. Epi Info 3.5.1. was used for the statistical analysis of age, sex, visual acuity, causes of blindness and visual impairment, and etiologies. Fifty six people were examined: 37 men (66.1%) and 19 women (33.9%). Their mean age was 21.57 ± 10.53 years (min-max: 5-49), and 48.2% were in the 10-19 years age group (n = 27). In all, 87.5% were blind, 7.14% severely visually impaired, and 1.78% moderately visually impaired. The main causes of blindness and visual impairment in our sample were corneal disease (32.14%), optic nerve lesions (26.78%), cataract and its surgical complications (19.64%), retinal disorders (10.71%), glaucoma (8.92%, and malformations of the eyeball (1.78%). Their etiologies included congenital cataracts (19.64%), meningitis/fever (8.92%), glaucoma (7.14%), measles (5.35%), ocular trauma (5.35%), albinism (3.57%), Lyell syndrome (1.8%), and alcohol ingestion (1.8%). Etiology was unknown in 46.42%. Fifty per cent of these causes of blindness and visual impairment were treatable and/or preventable. Corneal lesions were the main cause of blindness and visual impairment in our sample. Fifty per cent of the causes found were treatable and/or preventable. Thus, substantial efforts are required to ensure access to better quality specialist ocular care. Furthermore, local authorities should create more centers specialised in the rehabilitation of the visual handicapped.